2019
DOI: 10.3390/genes10090712
|View full text |Cite
|
Sign up to set email alerts
|

The Pituitary Transcriptional Response Related to Feed Conversion in Pigs

Abstract: Over the decades, pig breeding objectives have focused on improving the meat content in the carcass without taking into consideration the more effective fattening indicators that affect feed conversion. At present, pig growth traits associated particularly with animal feeding have become crucial due to their economic significance. This is especially evident in countries where pigs are maintained on large farms. The present study indicates that pituitary differentially expressed genes (DEGs) are activated in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The RIN parameter values for all the RNA samples were over 7.5. cDNA libraries were prepared using TruSeq RNA Sample Preparation Kit v2 (Illumina, San Diego, CA, USA) with individual indexing. The sequencing was conducted on a HiScanSQ System (Illumina, San Diego, CA, USA) in single 85 bp cycles using TruSeq Kit v3-HS chemistry (Illumina, San Diego, CA, USA), as described by Piórkowska et al [24].…”
Section: Rna-sequencing Differentially Expressed Gene (Deg) and Varimentioning
confidence: 99%
See 1 more Smart Citation
“…The RIN parameter values for all the RNA samples were over 7.5. cDNA libraries were prepared using TruSeq RNA Sample Preparation Kit v2 (Illumina, San Diego, CA, USA) with individual indexing. The sequencing was conducted on a HiScanSQ System (Illumina, San Diego, CA, USA) in single 85 bp cycles using TruSeq Kit v3-HS chemistry (Illumina, San Diego, CA, USA), as described by Piórkowska et al [24].…”
Section: Rna-sequencing Differentially Expressed Gene (Deg) and Varimentioning
confidence: 99%
“…The sequence data (GSE122349) has been submitted to the Gene Expression Omnibus (GEO). Raw read processing was performed as described by Piórkowska et al [24]. Cleaned reads were represented by Fragments Per Kilobase of transcript per Million mapped reads (FPKM) values.…”
Section: Rna-sequencing Differentially Expressed Gene (Deg) and Varimentioning
confidence: 99%
“…Although the RVIS values from the genetic intolerance analysis suggest that the respective genes are relatively tolerant to changes in functional variation, there should be further research on the real functionality, since some genes may have influence on important features of GMPs. While high differentiation in one candidate, CAMK2B, seems even vital to maintain cellular functions [20,21], for example, ARRB1 has found to be involved in feed conversion in pigs [22], AIRE is an important pathway gene of auto-immune response [23], and CHST12 is differentially expressed in Oocytes after nuclear transfer in mice [24]. Nine of these SNPs are identified when the DA2 and DA3 subpopulation are involved in a pairwise comparison, three of them are between DA2 and 3 and five are between a DA unit and NR, indicating that there is detectable differentiation between the DA units and NR.…”
Section: Variation and Differentiation Within And Between The Gmp Poolsmentioning
confidence: 99%
“…Pérez-Montarelo et al [ 13 ] confirmed that the usage of network interaction based on hypothalamic transcriptome analysis could pinpoint candidate genes for fatness in pigs. The transcriptomic profiling of the swine pituitary showed the strong association of this gland with postnatal growth and development [ 14 ], and also with fatness-associated traits [ 15 ].…”
Section: Introductionmentioning
confidence: 99%